Secondary metabolites produced by endophytic fungi, Alternaria alternata, as potential inhibitors of the human immunodeficiency virus - Nzimande, Bruce; Kumalo, Hezekiel M.; Ndlovu, Sizwe I.; Mkhwanazi, Nompumelelo P. (Frontiers in Genetics, 2022)
Antiretroviral treatment has significantly reduced human immunodeficiency virus infection and mortality. However, the current treatment regimen is limited by adverse side effects, the emergence of drug resistance, and the inability to eliminate viral reservoirs. Here, fifteen endophytic fungi were isolated from Sclerocarya birrea and Hypoxis plants. Crude extracts of Alternaria alternata (strain ID PO4PR1, PO4PR2, and PO2PL1) of the fifteen isolate’s crude extracts showed anti-HIV-1 activity in TZM-bl cell line at inhibitory concentration (IC50) values ranging from 0.017 to 1.170 μg/ml. The three crude extracts also maintained the virus replication inhibition profile on PBMCs and CD4+ T cells at concentrations ranging from 0.3 to 50.2 ng/ml. Partial purification using the solid phase extraction and analysis with Gas Chromatography-Mass spectrophotometry showed a diverse profile. The bioactive compounds were identified based on peak area, retention time, similarity index. The major compounds from GC-MS analysis of A. Alternata revealed the existence of cyclotrisiloxane octamethyl (22.92%); Propaninitrile (16,67%); Pyrrolol[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methyl propyl) (10.42%); Silane, diethylethoxy(2-ethoxyethyloxy) (4.17%); Coumarin, 3,4-dihydro-4,5,7-trimethyl- 4,5,7-Trimethyl-2-chromanone (13.7%) and 1,2-Cyclobutanedicarbonitrile (2.08%) with previously reported biological activities such as antimicrobial, anti-inflammatory and antioxidant properties. Therefore, these bioactive compounds from A. alternata fungal endophytes could be repurposed as potential anti-HIV agents. This study showed the potential of endophytic fungi, Alternaria alternata from S. birrea, and Hypoxis species as producers of anti-HIV compounds.